Cell permeability and nuclear DNA staining by propidium iodide in basidiomycetous yeasts - Ning Zhang (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Non-model yeasts within basidiomycetes have considerable importance in agriculture, industry, and environment, but they are not as well studied as ascomycetous yeasts. Serving as a basic technique, nuclear DNA staining is widely used in physiology, ecology, cell biology, and genetics. However, it is unclear whether the classical nuclear DNA staining method for ascomycetous yeasts is applicable to basidiomycetous yeasts. In this study, 5 yeasts ineffectively stained by the classical propidium iodide (PI) staining method were identified from 23 representative basidiomycetous yeasts. Pretreatment of cells using dimethyl sulfoxide (DMSO) or snailase markedly improved cell penetration to PI and thus enabled DNA content determination by flow cytometry on the recalcitrant yeasts. The pretreatments are efficient, simple, and fast, avoiding tedious mutagenesis or genetic engineering used in previous reports. The heterogeneity of cell penetration to PI among basidiomycetous yeasts was attributed to the discrepancy in cell wall polysaccharides instead of capsule or plasma membrane. This study also indicated that care must be taken in attributing PI-negative staining as viable cells when studying non-model microorganisms.